Vitrification and Crystallization of Phase-Separated Metallic Liquid - Yun Cheng; Wenchao Cui; Li Wang; Chuanxiao Peng; Shenghai Wang; Yuyang Wang (Metals, 2017)
The liquid–liquid phase separation (LLPS) behavior of Fe50Cu50 melt from 3500 K to 300 K with different rapid quenching is investigated by molecular dynamics (MD) simulation based on the embedded atom method (EAM). The liquid undergoes metastable phase separation by spinodal decomposition in the undercooled regime and subsequently solidifies into three different Fe-rich microstructures: the interconnected-type structure is kept in the glass and crystal at a higher cooling rate, while the Fe-rich droplets are found to crystalize at a lower cooling rate. During the crystallization process, only Fe-rich clusters can act as the solid nuclei. The twinning planes can be observed in the crystal and only the homogeneous atomic stacking shows mirror symmetry along the twinning boundary. Our present work provides atomic-scale understanding of LLPS melt during the cooling process.